Las exploraciones botánicas en Colombia: Una revisión al legado botánico literario con análisis de las colecciones de Lamiaceae como estudio de caso - Villamil-Montero, Daniel Antonio [UNESP]; Ming, Lin Chau [UNESP] (My University, 2016)
A chronological review of botanical explorations in Colombian was made through the revision of notes and publications from early 1500´s to late 1990´s. Complementary, herbaria photographs of Lamiaceae collections from botanical explorations in Colombia, deposited in the New York Botanical Garden Herbarium were analyzed in order to have a clear idea about the researches that were involved with collections in Colombia during the last 150 years.
The botanical explorations in Colombia: A review of the written botanical heritage with analyses of Lamiaceae collections as studied case
Keywords: Collectors; Expeditions; Historical botany; Labiatae; Naturalist; New Granada